Making Sense of Design Research: The Search for a Database - Meredith Davis (Artifact, 2007)
Abstract If you are a design researcher or graduate student who enters the keyword “branding” into the typical university library catalogue search engine, you will be as likely to yield books on cattle as on corporate identity. Or if you are a practitioner and want to locate one of the doctoral dissertations on design, completed in a handful of research-oriented PhD programs around the world, you will need a pretty good idea of the title or researcher’s name to find it. And if you are design faculty and find it necessary to access work in non-design disciplines that might be relevant to your scholarship, you will be on your own to winnow the titles from hundreds of books within a Library of Congress topical category to find something truly useful to design. In other words, there are no current databases on design research and few design-sensitive keywords that drive other disciplinary search engines. This work proposes a solution to that dilemma.